1983
DOI: 10.1111/j.1365-2133.1983.tb04597.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lymphocyte function following long-term PUVA therapy for psoriasis

Abstract: The surface markers and function of peripheral blood lymphocytes were examined in patients on long-term therapy with methoxsalen and UV-A radiation (PUVA). Ten patients with psoriasis were selected because they had received a high exposure to PUVA therapy, i.e., more than 200 treatments over 2-6 years with cumulative exposure doses of 1700-6000 J/cm2 UV-A radiation. Results were compared to those obtained with lymphocytes from untreated patients and UV-B treated patients with psoriasis. The PUVA-treated patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…It has already been reported that PUVA therapy downregulates the immune response both in vivo (2)(3)(4)(5)(6)(8)(9)(10) and in vitro (7). We demonstrated here that PUVA therapy not only downregulates T-cell function but also suppresses the expression of cell adhesion molecules of T lymphocytes in vitro.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has already been reported that PUVA therapy downregulates the immune response both in vivo (2)(3)(4)(5)(6)(8)(9)(10) and in vitro (7). We demonstrated here that PUVA therapy not only downregulates T-cell function but also suppresses the expression of cell adhesion molecules of T lymphocytes in vitro.…”
Section: Discussionsupporting
confidence: 62%
“…One of the therapeutic effects of PUVA on psoriasis vulgaris appears to be the inhibition of cell rephcation by the photoconjugation of psoralens with DNA of epidermal keratinocytes and dermal cells including endothelial cells (1). On the other hand, effects of PUVA therapy on circulating lymphocytes have also been indicated; namely, reduction in the numbers of circulating Erosette-forming lymphocytes (2), improvement of T-cell levels assessed by E-rosettes (3,4) and reduction in the number of circulating helper/inducer T cells (OKT4) (5). PUVA also inhibits DNA synthesis of circulating lymphocytes in vivo (6), and reduces cell-mediated immune responses (7) and delayed cutaneous hypersensitivity (2,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the nonlethal immune-modulating effects, however, should be short-lived, suggesting that long-term benefits (months to years) derived from PUVA treatment of diseases such as psoriasis and CTCL m a y be based, instead, in the ability of P U V A to delete activated T-cell clones, which are preferentially located in the skin (24). In psoriasis, PUVA treatment depletes >90% of T-lymphocytes infiltrating cutaneous lesions (3), but comparatively small effects are produced o n circulating T-lymphocytes (25)(26)(27). Hence the ability of P U V A to deplete o r eliminate specific intracutaneous T-cell clones by direct cytotoxic actions may underlie its ability t o induce disease remissions in diseases such as psoriasis and CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…12, 13 These patients have been reported to have decreased immunization rates to contact allergens, 14, 15 and reduced numbers of circulating peripheral blood CD4 + T-cells. 16, 17 …”
Section: Evidence Of Photoimmunological Effects Of Uv Radiation In Humentioning
confidence: 99%